Comparing the performance of the common used eumycetoma diagnostic tests. Issue 5 (17th January 2023) - Siddig, Emmanuel Edwar; Nyuykonge, Bertrand; Mhmoud, Najwa Adam; Abdallah, Omnia Babekir; Bahar, Mustafa El Nour; Ahmed, Eiman Siddig; Nyaoke, Borna; Zijlstra, Eduard E.; Verbon, Annelies; Bakhiet, Sahar Mubarak; Fahal, Ahmed Hassan; van de Sande, Wendy W. J.
Abstract: Objectives: Mycetoma is a neglected tropical implantation disease caused by 70 different infectious agents. Identifying the causative organism to the species level is essential for appropriate patient management. Ultrasound, histopathology, culture and two species‐specific PCRs are most the commonly used methods for species identification in endemic regions. The aim of this study was to compare the diagnostic performance of these commonly used assays using sequencing of barcoding genes as the gold standard. Methods: This descriptive cross‐sectional study was conducted at the Mycetoma Research Centre, University of Khartoum, Sudan. It included 222 patients suspected of fungal mycetoma caused by Madurella mycetomatis . Results: 154 (69.3%) were correctly identified by ultrasound, histology, culture and both species‐specific PCRs. In 60 patients, at least one of the diagnostic tests failed to identify M. mycetomatis . Five patients had no evidence of eumycetoma, and for three, only the ultrasound was indicative of mycetoma. The two species‐specific PCRs were the most sensitive and specific methods, followed by culture and histology. Ultrasound was the least specific as it only allowed differentiation between actinomycetoma and eumycetoma. The time to result was 9.38 minutes for ultrasound, 3.76 hours for PCR, 8.5 days for histopathology and 21 days for grain culturing. Conclusion: Currently, PCR directly on DNA isolated from grains is the most rapid and reliable diagnostic tool to identify M. mycetomatis eumycetoma.